DIGITAL ECOSYSTEM AND PENTAHELIX SYNERGY IN BUILDING UMKM SUSTAINABILITY IN MALANG CITY - Mulyaningtyas, Mulyaningtyas; Wardana, Ditya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to analyze the Sustainability of MSMEs in Malang City.  The data from the analysis is then used to describe the condition of the digital ecosystem and pentahelix synergy in building sustainability for Malang City MSMEs. This research was conducted using a quantitative descriptive method to formulate the role of the digital ecosystem and pentahelix. Data was obtained using questionnaire distribution techniques, observation and documentation. The data was organized into value score categories, then averaged the scores of each variable and analyzed the score weights so that the research results showed that the widespread adoption of digital technology improves business operational efficiency through the use of social media for marketing, digital technology in transactions, and paid digital marketing. However, there are challenges in collaboration with academics and government support that still need to be strengthened to maximize the potential of Pentahelix collaboration